Accretion disc reverberation mapping in a high-redshift quasar - Pozo Nuñez, Francisco; Bañados Torres, Eduardo; Panda, S.; Heidt, Jochen (Astronomy and astrophysics, 2025)
Powered by supermassive black holes at their centers, quasars are among the most luminous objects in the Universe, serving as important probes of cosmic history and galaxy evolution. The size of the accretion disc surrounding the black hole is a critical parameter for understanding quasar physics and their potential use as standard candles in cosmology. However, direct measurements of accretion disc sizes have so far been confined to the Local Universe (z < 0.2), limiting our understanding of quasars during the peak of cosmic activity. Here, we report the first direct measurement of the accretion disc size in the quasar QSO J0455-4216 at z = 2.66, when the Universe was only ∼2 Gyrs old. Medium-band filters mounted on the MPG/ESO 2.2-metre telescope at La Silla Observatory were used to isolate continuum emission regions during a six-month monitoring campaign. The light curves exhibit pronounced variability features and enabled the detection of inter-band time delays from different parts of the disc. We mapped the disc and located its ultraviolet-emitting outermost region at light-days from the black hole (∼500 AU). Given a supermassive black hole 900 million times the mass of the Sun, these measurements validate accretion disc theory at an unprecedented redshift and pave the way for efficient black hole mass estimates, reducing decades-long spectroscopic reverberation campaigns to just a few years or less.
Gesehen am 10.12.2025